2008
DOI: 10.1021/jf8012053
|View full text |Cite
|
Sign up to set email alerts
|

Betalains in Red and Yellow Varieties of the Andean Tuber Crop Ulluco (Ullucus tuberosus)

Abstract: The betalain pigments in ulluco (Ullucus tuberosus), a tuberous crop native to the Andes, have been investigated for the first time using LC-DAD-ESI-MS-MS(2) analyses. Five red, yellow, and red-spotted accessions introduced into New Zealand as a new food crop plus two red tetraploid lines were investigated. Thirty-two different betalains were identified. Both the yellow and red tubers were rich in yellow betaxanthins, and the most prominent among the 20 identified were histidine-betaxanthin, arginine-betaxanth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 29 publications
4
37
0
5
Order By: Relevance
“…Betalain molecules displays wide range of hues, betacyanins have reddish-violet colour while betaxanthins have a general yellow-orange colour (Albano et al, 2015;Esquivel, 2016;Gandía-herrero et al, 2013;Gandía-Herrero et al, 2010), the latter being only identified in OG and OS samples. Five betacyanins were identified, betanidin-5-O-β-sophoroside, betanidin-5-O-β-glucoside (betanin), isobetanin, gomphrenin I and betanidin (peaks 3, 4, 5, 6 and 7, respectively), having been previously identified by other authors (CastellanosSantiago and Yahia, 2008;Morales et al, 2015Morales et al, , 2014Stintzing et al, 2002;Svenson et al, 2008). On the contrary of betaxanthins, betacianins fraction was found in higher quantities in OE samples, being peak 4 (betanin) the main compound found (14.9 mg/g extract), This characteristic can be easily predicted due to the strong violet hue present in OE and also because betanin (betanidin-5-O-β-glucoside) is the most widespread betacyanin among plants (Esatbeyoglu et al, 2014).…”
Section: Phenolic and Betalain Compositionsupporting
confidence: 54%
See 1 more Smart Citation
“…Betalain molecules displays wide range of hues, betacyanins have reddish-violet colour while betaxanthins have a general yellow-orange colour (Albano et al, 2015;Esquivel, 2016;Gandía-herrero et al, 2013;Gandía-Herrero et al, 2010), the latter being only identified in OG and OS samples. Five betacyanins were identified, betanidin-5-O-β-sophoroside, betanidin-5-O-β-glucoside (betanin), isobetanin, gomphrenin I and betanidin (peaks 3, 4, 5, 6 and 7, respectively), having been previously identified by other authors (CastellanosSantiago and Yahia, 2008;Morales et al, 2015Morales et al, , 2014Stintzing et al, 2002;Svenson et al, 2008). On the contrary of betaxanthins, betacianins fraction was found in higher quantities in OE samples, being peak 4 (betanin) the main compound found (14.9 mg/g extract), This characteristic can be easily predicted due to the strong violet hue present in OE and also because betanin (betanidin-5-O-β-glucoside) is the most widespread betacyanin among plants (Esatbeyoglu et al, 2014).…”
Section: Phenolic and Betalain Compositionsupporting
confidence: 54%
“…cultivars and also by Svenson et al (2008) in Ullucus tuberosus fruits. Betalain molecules displays wide range of hues, betacyanins have reddish-violet colour while betaxanthins have a general yellow-orange colour (Albano et al, 2015;Esquivel, 2016;Gandía-herrero et al, 2013;Gandía-Herrero et al, 2010), the latter being only identified in OG and OS samples.…”
Section: Phenolic and Betalain Compositionmentioning
confidence: 89%
“…The UV-vis spectra were recorded from 360-800 nm in order to develop a photometric quantification of betalains, according to the method proposed by (Svenson, Smallfield, Joyce, Sansom, & Perry, 2008). Maximum absorbance of 484 and 535 nm was reported to quantify betaxanthins and betacyanins, respectively.…”
Section: Spectrophotometric Quantification Of Betalainsmentioning
confidence: 99%
“…En la actualidad, se estima que alrededor de 30 millones de personas en los Andes consumen ulluco (Hermann & Heller 1997). Fuera de los Andes, el cultivo comercial del ulluco ha logrado ser exitoso en Nueva Zelanda (Busch et al 2000, Svenson et al 2008). …”
Section: Presentaciónunclassified
“…Svenson et al (2008) han reportado la presencia de 32 tipos de betalaínas en ulluco, 20 de ellas del tipo betaxantina (responsables del color amarillo y anaranjado) y las 12 restantes del tipo betacianina (responsables del color rojo y púrpura). Estos pigmentos carecen casi por completo de actividad antioxidante y por esta razón la oca, la papa y la mashua constituyen fuentes mucho más abundantes de compuestos antioxidantes (Campos et al 2006).…”
Section: Presentaciónunclassified